Pengaruh Audit Tenure, Komite Audit Dan Audit Capacity Stress Terhadap Kualitas Audit - Stephanie Yolanda; Fefri Indra Arza; Halmawati Halmawati (Universitas Negeri Padang, 2019)
This study aims to determine the effect of the audit tenure, audit committee, and audit capacity stress on audit quality as measured by earnings surprise benchmark approach. The research used secondary data. The population was all manufacturing companies listed in Indonesia Stock Exchange in the period of 2015-2017. The data collection technique used is purposive sampling and 303 samples obtained data. The independent variables were audit tenure, audit committee, and audit capacity stress at the significance level of 5%. This study using logistic regression analysis techniques. The result of the research showed that audit tenure had no significant influence on audit quality with a significance level that is equal to 0.145, audit committee had no significant influence on audit quality a significance level that is equal to 0.652, and audit capacity stress had no significant influence on audit quality a significance level that is equal to 0.522 of the manufacturing companies listed in Indonesia Stock Exchange